PENGARUH PENGGUNAAN MEDIA LABORATORIUM VIRTUAL FISIKA TERHADAP KEMAMPUAN PEMECAHAN MASALAH SISWA - Darti, Enti Yuyun; Fuaddunazmi, Muhammad; Prasetya, Dwi Sabda Budi (IKIP Mataram, 2015)
Physics is one of the subjects taunght in SMPN 4 Praya Tengah. The Instructional media which used is still relatively conventional with teaching materials such as text books. This study used a learning media of animation software in a virtual learning environment to enhance the problem solving ability of students. This study was a quasi-eksperimental study. The study also included into the study of population, because the entrie student population used in the study. The data analysis technigue which used was the t-test. The results obtained are tcaculate = 2,87 and ttable = 1,72. because tcaculate its count greater than ttable it can be concluded that there are impact of using the virtual media laboratory of physics to student’s problem-solving abilites.